Selection and potential aquaculture of â€œwaderâ€ fish of the Genus Rasbora - AGUNG BUDIHARJO (Society for Indonesian Biodiversity, 2002)
â€œWaderâ€ fish is one of the local Indonesian wild fish that not cultured yet. This fish have amount of species, included Genus Rasbora. The aim of this research was to known the â€œwaderâ€ fish diversity of Genus Rasbora that potentially to aquaculture. The research conducted in 10 weeks to three species, namely R. lateristriata, R. aprotaenia, and R. argyrotaenia. The research was designed in two treatments, namely giving pellet and non-giving pellet. The growth data was measured every week. The result indicated that pellet could increase size and growth of the fish. R. argyrotaenia had bigger size and faster growth than R. lateristriata and R. aprotaenia. The optimum growth of R. argyrotaenia occured at third to sixth weeks, and it got maximum size at seventh week. So it was suitable toaquaculture.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: selection, potential aquaculture, Rasbora, R. lateristriata, R. aprotaenia, R. argyrotaenia.